Audit quality, audit opinion, and earnings management: Indonesian evidence - Krismiaji, Krismiaji; Sumayyah, Sumayyah (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
Abstract: This research investigates the role of audit quality as moderation on the association between audit opinions and accrual earnings. The sample used in this study is Indonesian companies listed on the Indonesian Stock Exchange (IDX) during 2016 – 2020. The study uses Generalized Least Squares (GLS) regression models to process data. The results show that audit opinions are positively associated with earnings management. When audit quality is examined individually, it negatively affects earnings management. Moreover, when it interacted with audit opinions, the interaction variables negatively affect earnings management. This study contributes to the current literature about auditing and earnings management practices as well as the initial work to investigate the relationship between audit opinion and earnings management, by involving audit quality as a moderation. This study enriches the existing literature about audit opinion, audit quality, and earnings management, especially in the context of an emerging market.